Perovskite solar cells for energy harvesting in low-light environments - Ibrahim, Izzah Afifah; Mohamad Azmi, Muhammad Fakhrullah; Ismadi, Irfan Danial; Redzuan, Muhammad Fadzlisyam; Mohd Noor, Ikhwan Syafiq; Mohd Ghazali, Mohd Ifwat; Abd Majid, Wan Haliza; Abdullah, Shahino Mah (Universiti Teknologi MARA, Negeri Sembilan, 2025)
The transition from fossil fuels to renewable energy is critical to reducing air pollution and mitigating climate change. Solar energy, as a clean and sustainable alternative, has gained significant attention, with perovskite solar cells emerging as a promising technology. These cells offer several advantages over traditional silicon-based photovoltaics, including higher efficiency potential, lower production costs, and simpler manufacturing processes. Recent research highlights the feasibility of perovskite solar cells for indoor and low-light energy harvesting, demonstrating their versatility beyond conventional outdoor applications. In this study, a solution-processed perovskite solar cell was fabricated and tested under room building light conditions. The device achieved an impressive open-circuit voltage of 1.49V and a short-circuit current density of 5.15 mA/cm², with a maximum power conversion efficiency of 18.67%. These results underscore the potential of perovskite solar cells to efficiently generate electricity even in ambient lighting, making them ideal for powering IoT devices, smart sensors, and other low-energy electronics indoors. The cost-effective production and high efficiency of perovskite solar cells position them as a key player in the renewable energy transition. Their ability to perform well under varied lighting conditions expands their applicability, supporting decentralized energy generation and reducing reliance on fossil fuels. Further advancements in stability and scalability could accelerate their commercialization, contributing to a more sustainable energy future. By harnessing indoor light, perovskite technology complements traditional solar panels, enhancing energy accessibility and driving the shift toward cleaner power solutions.